Global Reporting Initiative and social impact in managing corporate responsibility: a case study of three multinationals in the forest industry - Toppinen, A.; Korhonen-Kurki, Kaisa (Wiley, 2013)
We examine recent evolution in corporate responsibility in the forest industry, an important natural‐resource‐based industry which is under rapid internationalisation and structural change under challenging financial pressures. We address two recent trends in corporate communication: corporate disclosure, that is the adoption of consistent external reporting standards [namely the Global Reporting Initiative (GRI) ], and the growing awareness of engagement with and impact on local communities through philanthropy, generation of prosperity, communication and the social impact of core activities. This study uses a comparative qualitative case approach to forest industry multinational enterprises (MNEs) based on a combination of secondary (reporting, company newsletters and other documentation) and interview data. Three large‐scale multinational forest industry firms, all pursuing different strategies in terms of internationalisation and geographical and product diversification, were chosen for the study: Stora Enso, SCA and Sappi Ltd. Our results show that the overall quality of sustainability reporting has improved in these companies from 2005 to 2009 with the adoption of GRI. However, based on our fourfold categorisation of social impact, the core social impact indicator in GRI (SO1) has been interpreted very differently in these MNEs, and the adoption of GRI has not actually much improved the comparability of the reports or transparency of practices.